POLICY OF THE FISHERIES AND MARINE SERVICES IN INCREASING REGIONAL ORIGINAL INCOME IN BARRU DISTRICT - Marsuki Marsuki; Asriani Asriani; Tasniah Tasniah (Jurnal Scientia, 2023)
This research aims to determine the government policy of the Maritime and Fisheries Service in increasing regional income in Barru Regency and the factors that support and hinder the Barru Regency Maritime and Fisheries Service in increasing local original income in Barru. The type of research used is quantitative research. The research location is at the Maritime Affairs and Fisheries Service office. Data sources were obtained by means of questionnaires, observation and documentation. The data analysis method uses the SPSS application. The results of this research show: The Maritime Affairs and Fisheries Service Policy in Increasing Original Regional Income in Barru Regency is good and measurable as seen from several supporting fisheries and marine policy indicators, namely capture and aquaculture, economic structure, facilities and fishing infrastructure, licensing system and institutions and human resources. The factors that influence fisheries and marine policy are supporting factors and inhibiting factors.